2021
DOI: 10.1155/2021/6671130
|View full text |Cite
|
Sign up to set email alerts
|

Ethanolic Extract of Centella asiatica Treatment in the Early Stage of Hyperglycemia Condition Inhibits Glomerular Injury and Vascular Remodeling in Diabetic Rat Model

Abstract: Background. Diabetes mellitus (DM) is marked by oxidative stress, inflammation, and vascular dysfunction that caused diabetic nephropathy that resulted in end-stage renal disease (ESRD). Vascular dysfunction is characterized by an imbalance in vasoconstrictor and vasodilator agents which underlies the mechanism of vascular injury in DM. Additionally, diminished podocytes correlate with the severity of kidney injury. Podocyturia often precedes proteinuria in several kidney diseases, including diabetic kidney di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 68 publications
0
4
0
2
Order By: Relevance
“…CA reduced vascular remodelling, glomeruli injury by increasing antifibrotic factor activity, and inflammatory biomarkers restored renal injury in nephrectomy animals. [21][22][23] Different protective mechanisms could be responsible for Centella asiatica's nephroprotective effects. Previous research suggested that triterpenoid present in CA increased the activity of antioxidant enzymes and nuclear factor erythroid-2-related factor 2.…”
Section: Discussionmentioning
confidence: 99%
“…CA reduced vascular remodelling, glomeruli injury by increasing antifibrotic factor activity, and inflammatory biomarkers restored renal injury in nephrectomy animals. [21][22][23] Different protective mechanisms could be responsible for Centella asiatica's nephroprotective effects. Previous research suggested that triterpenoid present in CA increased the activity of antioxidant enzymes and nuclear factor erythroid-2-related factor 2.…”
Section: Discussionmentioning
confidence: 99%
“…Proteinuria is often accompanied by the shedding of podocytes from the basement membrane. Studies have shown that podocyteuria often precedes proteinuria in several renal diseases including DKD [ 19 ]. Therefore, detection of urine containing exfoliated podocytes plays a role in the early diagnosis of DKD [ 20 ].…”
Section: The Roles Of Podocyte In Proteinuria and Podocyteuriamentioning
confidence: 99%
“…Salah satunya responden yang memiliki penyakit penyerta. Mereka yang memiliki penyakit komorbid harus dalam kondisi terkontrol, Hal ini disebabkan orang-orang yang memiliki penyakit tertentu tidak memiliki daya tahan yang baik untuk membuat antibodi (Setyaningsih et al, 2021). Setiap vaksin COVID-19 mempunyai keunggulan dan kelemahan, baik dalam efektifitas, keamanan dan penyimpanan (Pawankar et al, 2021).…”
Section: Pembahasanunclassified